دور السياسات الاقتصادية في تحفيز الاستثمار الكلي في سورية - العربيد, عدنان; وقاف, حسين (Latakia University Journal - Economic and Legal Sciences Series, 2015)
بما أن موضوع تدخل الدولة في الحياة الاقتصادية من المواضيع التي تثير الكثير من الجدل والنقاش، وبما أنه هناك الكثير من التساؤل عن مدى فعالية هذا التدخل في التأثير على النشاط الاقتصادي وتشجيعه، وهذا البحث يناقش هذا الموضوع بهدف تبيان أهمية وفاعلية التدخل الحكومي في تشجيع الاستثمار الكلي من خلال دراسة فعالية السياسات الاقتصادية الحكومية وتحديداً السياستين المالية والنقدية في التأثير على الحجم الكلي للاستثمار باعتبار أن الاستثمار يعتبر حجر الزاوية في أية تنمية اقتصادية في الحاضر والمستقبل، ويعتمد البحث المنهج الوصفي التحليلي كما يستخدم أسلوب التحليل الاحصائي للبيانات من أجل تحقيق هذه الأهداف، وتبين من خلال البحث الدور الهام للسياسة المالية والسياسة التجارية في تشجيع الاستثمار الكلي بينما لوحظ غياب دور السياسة النقدية كما تبين وجود العديد من المتغيرات الهامة التي لم تدخل ضمن النموذج ومن أهمها متغيري الادخار والإنفاق الحكومي الجاري، هذا ويتناول البحث حالة الجمهورية العربية السورية خلال الفترة (1980-2010). Since the subject of state intervention in the economic life is one topic that excites a lot of controversy and debate, there was a lot of questions about the effectiveness of this intervention in influencing and encouraging the economic activity. The paper discusses this issue in order to demonstrate the importance and effectiveness of government intervention in the promotion of the overall investment through the study of the effectiveness of government economic policies, specifically fiscal and monetary policies in effect on the overall size of the investment, given that the investment is a cornerstone of any economic development in the present and the future. It adopts the descriptive analytical method as a method of statistical analysis of the data in order to achieve these goals, and show the important role of fiscal policy and trade policy to encourage the total investment. However, it is observed the absence of the role of monetary policy and that there are many important variables that were not included in the model. The most important variables are those of savings and public current expenditure. This research deals with the case of the Syrian Arab Republic during the period (1980-2010).